Gothic passages : racial ambiguity and the American gothic - Edwards, Justin D., 1970- (University of Iowa Press, 2003)
This groundbreaking study analyzes the development of American gothic literature alongside nineteenth-century discourses of passing and racial ambiguity. By bringing together these areas of analysis, Justin Edwards considers the following questions. How are the categories of "race" and the rhetoric of racial difference tied to the language of gothicism? What can these discursive ties tell us about a range of social boundaries - gender, sexuality, class, race, etc. - during the nineteenth century? What can the construction and destabilization of these social boundarie